Shortening university career fades the signal away. Evidence from Italy - Carolina Castagnetti; Silvia Dal Bianco; Luisa Rosti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
Italian university system was reformed in 2001. This paper tests the screening role of degree scores for 2004-Italian graduates. We find support of the strong screening hypothesis for prereform type degrees, while we do not find any evidence of signalling effects for post-reform 3-years degrees. We gauge that the shutting down of the signal can be partially ascribed to the poor quality of students who obtained a 3-years degree without taking any further education.
Keywords: I23; J08; 330; Screening; Italy; Higher Education